2022
DOI: 10.1002/aenm.202200666
|View full text |Cite|
|
Sign up to set email alerts
|

A Multifaceted Ferrocene Interlayer for Highly Stable and Efficient Lithium Doped Spiro‐OMeTAD‐based Perovskite Solar Cells

Abstract: hole mobilities within the HTL of up to 1.6 × 10 -3 cm 2 V -1 s -1 . [4] However, the use of such highly hygroscopic lithium salts has been shown to dramatically accelerate the degradation of PSCs. [5][6][7][8] Previous works have identified that upon doping with LiTFSI, lithium ions can readily become mobile and diffuse within the perovskite layer, forming hygroscopic LiX salts (where Xis a halide) which in turn rapidly degrade the perovskite. [5,[9][10][11][12][13][14] Wang et al demonstrated that following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 81 publications
(168 reference statements)
0
22
0
Order By: Relevance
“…To investigate thermal stability, the PSCs were aged under ISOS-T-1 conditions. [40,41] The PSPP device retained 84 % of the initial PCE after the aging test of heating at 60 °C with 40 % RH for 1224 h, compared with 59 % for the control PSC (Figure 5b). Notably, the PSCs in the aforementioned aging test employed LiTFSI and 4-tert-butylpyridine co-doped spiro-OMeTAD as the hole transport layer.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate thermal stability, the PSCs were aged under ISOS-T-1 conditions. [40,41] The PSPP device retained 84 % of the initial PCE after the aging test of heating at 60 °C with 40 % RH for 1224 h, compared with 59 % for the control PSC (Figure 5b). Notably, the PSCs in the aforementioned aging test employed LiTFSI and 4-tert-butylpyridine co-doped spiro-OMeTAD as the hole transport layer.…”
Section: Methodsmentioning
confidence: 99%
“…[80] We also exploited ferrocene as a perovskite surface potential modifier at (FAPbI 3 ) 0.95 (MAPbBr 3 ) 0.05 /spiro-OMeTAD (HTL) junctions. [81] This avenue yielded i) enhanced charge transfer from perovskite to spiro-OMeTAD (Figure 7d,e) and ii) highly efficient solar cells (23.45 %) with high operational stability (70 % performance retention after 1250 h). Similarly, we demonstrated that ultrathin polymethylmethacrylate (PMMA) interlayers can effectively enhance selectivity at PEDOT:PSS/(PEA) 0.2 (FA) 0.8 SnI 3 interfaces and boost solar cell performance from 6.5 % to 10 % (Figure 7f).…”
Section: Interfacial Engineeringmentioning
confidence: 99%
“…16 In addition to the structural design and modification aimed at the HTL itself and its dopant composition, selecting suitable Li + migration inhibitors to modify and regulate the interface between the perovskite and HTL layer is also a potential method to inhibit Li + migration. 17 Besides Li + migration, there exist potential barriers at the perovskite/spiro-OMeTAD interface, which lead to energy loss and the impeding of hole extraction. 18 Choosing suitable Li + migration inhibitors as interface modifiers can not only inhibit Li + migration, but can also take the stability and charge extraction properties of the perovskite/HTL interface into consideration, which is of great significance for further improving device stability.…”
Section: Introductionmentioning
confidence: 99%